Effect of Supplementation of Geloi (TinosporaCordifolia) Stem Powder and Ascorbic Acid on Economics of Broiler Production in Arid Zone of Rajasthan - Jain, D; Dhuria, R. K.; Sharma, T.; Bothra, T.; Prajapat, Umesh Kumar (Indian Journal of Animal Nutrition, 2020)
A 42 day feeding trial was carried out to investigate the effect of dietary addition of graded levels of Tinospora cordifolia stem powder with or without ascorbic acid on economics of broiler production using 360 one-day-old broiler chicks in 5Ã—2 factorial experiment within a completely randomized design and divided into ten (10) dietary treatments groups (T1-T10) in triplicate of twelve chicks per replicate. Environment stress was observed during feeding trial as ambient temperature and THI were recorded on higher side than the threshold level during the entire experimental period. The findings of comparative economics of broiler production indicated that addition of Geloi at graded levels and ascorbic acid alone or in combinations reduced the overall cost of feed per kg gain as compared to control but maximum reduction in overall cost of feed per kg gain was obtained in T7 treatment group containing 0.25% of Geloi supplemented with ascorbic acid i.e. 11.03% reduction.